Prostaglandin EP4 receptor mRNA expression in canine lymphoma. (16th July 2021) - Musser, Margaret L.; Viall, Austin K.; Phillips, Rachel L.; Fasina, Olufemi; Johannes, Chad M.
Abstract: Canine lymphoma (LSA) is a diverse, aggressive malignancy initiated by a variety of factors. Understanding those factors could help identify potential treatment options. Chronic inflammation drives lymphoma in human medicine and is suspected to play a role in veterinary medicine. The exact mechanisms, however, have not been elucidated. Upregulation of the cyclooxygenase enzymes, and subsequently prostaglandins, potentially play a stimulatory role. Prostaglandins work through one of four EP receptors (EP1‐EP4) and the effects mediated through EP4R specifically are thought to be the primary drivers of cancer development. In human T‐cell LSA, overexpression of EP4R has been found and appears to protect LSA cells from apoptosis. The role of EP4R in human B‐cell LSA is more nuanced. This study aims to evaluate the mRNA expression of the EP4R gene ( ptger4 ) in canine B‐cell and T‐cell LSA. Archived canine lymph nodes with histologically confirmed B‐cell and T‐cell LSA, and reactive lymph nodes, were evaluated for EP4R mRNA expression using a novel RNA in situ hybridization technique (RNAscope). Quantification of RNAscope signals was completed with an advanced digital pathology image analysis system (HALO). Results were reported as copy number, H‐score, and percent tumour cell expression of EP4R mRNA. All reactive, B‐cell LSA, and T‐cell LSA lymph nodes expressed EP4R mRNA. The mRNA copy number, H‐score, and percent tumour cell expression of EP4R were higher in B‐cell ( p < .003) and T‐cell ( p < .001) LSA samples compared to reactive lymph node samples. There were no differences between B‐cell LSA and T‐cell LSA.